The pump industry – past, present and future. Issue 2 (February 2016) - Wilson, Andy
Abstract : This is the next article in a series supporting the British Pump Manufacturers Association's 75th anniversary in 2016. The liquid pump was a key technological development, and here pump provider Hidrostal explores its history and where pump efficiency standards look to be heading in the future.